2008
DOI: 10.1007/s00262-008-0510-9
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of a T helper cell supported CTL response induced by a survivin peptide vaccine against murine cerebral glioma

Abstract: Survivin is a tumor-associated antigen (TAA) that has significant potential for use as a cancer vaccine target. To identify survivin epitopes that might serve as targets for CTL-mediated, anti-tumor responses, we evaluated a series of survivin peptides with predicted binding to mouse H2-K b and human HLA-A201 antigens in peptide-loaded dendritic cell (DC) vaccines. H2-K b -positive, C57BL/ 6 mice were vaccinated using syngeneic, peptide-loaded DC2.4 cells. Splenocytes from vaccinated mice were screened by flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0
1

Year Published

2009
2009
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 27 publications
1
44
0
1
Order By: Relevance
“…The survivin protein is a member of the inhibitor-of-apoptosis (IAP) gene family and is expressed in almost all malignant tissues, but is not present in normal differentiated adult tissues [27]. In syngeneic tumor models immunization with DC loaded with survivin-derived peptides induced specific CTL and significantly prolonged survival or induced protective immunity against tumor challenge [28,29]. Furthermore, the presence of survivin-specific CTL has been detected in patients with various cancers, and vaccination with a HLA-A2 restricted survivin peptide was successful in a patient suffering from pancreatic cancer leading to complete remission of liver metastasis [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The survivin protein is a member of the inhibitor-of-apoptosis (IAP) gene family and is expressed in almost all malignant tissues, but is not present in normal differentiated adult tissues [27]. In syngeneic tumor models immunization with DC loaded with survivin-derived peptides induced specific CTL and significantly prolonged survival or induced protective immunity against tumor challenge [28,29]. Furthermore, the presence of survivin-specific CTL has been detected in patients with various cancers, and vaccination with a HLA-A2 restricted survivin peptide was successful in a patient suffering from pancreatic cancer leading to complete remission of liver metastasis [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The availability of multiple survivin epitopes presented by different HLA restriction elements further reduces the risk of immune escape and thereby might improve therapeutic effectiveness. While several survivin-derived CTL epitopes are known in humans [19,20,31,32], there are only limited reports for the murine system [27,33].…”
Section: Discussionmentioning
confidence: 99%
“…The availability of multiple survivin epitopes presented by different HLA restriction elements further reduces the risk of immune escape and thereby might improve therapeutic effectiveness. While several survivin-derived CTL epitopes are known in humans [19,20,31,32], there are only limited reports for the murine system [27,33].In the present study, we identified two H-2K were carried out as described [36]. The assembly assay is based on stabilization of the class I molecule after loading of peptide to the peptide transporter-deficient cell line RMA-S.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method was also applied for the development of a survivin-based immunotherapy against tumors such as breast cancer, colorectal cancer, gastric cancer or glioma. [40][41][42][43] We have previously shown that the syfpeithi prediction algorhithm 26 was reliable for the development of a minigene DNA vaccine encoding for murine tyrosine hydroxylase (mTH)-derived peptides. 21 In this report, the isolation of peptides presented by MHC class I molecules and the bioinformatical approach led to the generation of mTH minigene DNA vaccines equally effective in the induction of CTL-mediated antineuroblastoma immune responses.…”
Section: Cd8mentioning
confidence: 99%